TINJAUAN KETIDAKTEPATAN KODE DIAGNOSIS PENYAKIT DAN TINDAKAN MEDIS KASUS GIGI DAN MULUT RAWAT JALAN DI RUMAH SAKIT X JAKARTA - Indah Kristina; Rani Rahmayanti (APIKES Bhumi Husada Jakarta, 2023)
ABSTRACT This research is to identify the Standard Operating Procedure (SPO) coding, calculate the number of inaccuracies in the disease diagnosis code and medical treatment in outpatient dental and oral cases and the factors causing the code inaccuracy. The research method used is descriptive analysis research method with data collection techniques by observation and interviews. The population of this study amounted to 2141 medical records, especially in the clinical summary in November 2021-April 2022, samples taken as many as 96 clinical summaries. The results of the study: the SOP has been carried out but is in the process of being revised and not yet perfect, the inaccuracy rate of the incorrect disease diagnosis code is 29 (30.20%) and the correct one is 67 (69.80%), while the inaccurate medical code of action is 18 (18.75%) and the correct one is 78 (81.25%), Causing factors: SOP steps are not perfect, the competence of coding officers is still lacking, identification of medical diagnoses and actions is less detailed, and lack of evaluation, especially periodic coding audits. Bibliography : 17 (2006 – 2020) Keywords : Code, Diagnosis, Medical Action, Clinical Summary, Dental, Oral